A new combined parameter predicts re-treatment for coil-embolized aneurysms: a computational fluid dynamics multivariable analysis study - Fujimura, Soichiro (J Neurointerv Surg, 2018)
PURPOSE: Coil embolization is a minimally invasive method used to treat cerebral aneurysms. Although this endovascular treatment has a high success rate, aneurysmal re-treatment due to recanalization remains a major problem of this method. The purpose of this study was to determine a combined parameter that can be useful for predicting aneurysmal re-treatment due to recanalization. METHODS: Patient-specific geometries were used to retrospectively analyze the blood flow for 26 re-treated and 74 non-retreated aneurysms. Post-operatively aneurysms were evaluated at 12-month follow-up. The hemodynamic differences between the re-treatment and non-retreatment aneurysms were analyzed before and after coil embolization using computation fluid dynamics. Basic fluid characteristics, rates of change, morphological factors of aneurysms and patient-specific clinical information were examined. Multivariable analysis and logistic regression analysis were performed to determine a combined parameter—re-treatment predictor (RP). RESULTS: Among examined hemodynamic, morphological, and clinical parameters, slight reduction of blood flow velocity rate in the aneurysm, slight increase of pressure rate at the aneurysmal neck and neck area, and hypertension were the main factors contributing to re-treatment. Notably, hemodynamic parameters between re-treatment and non-retreatment groups before embolization were similar: however, we observed significant differences between the groups in the post-embolization average velocity and the rate of reduction in this velocity in the aneurysmal dome. CONCLUSIONS: The combined parameter, RP, which takes into consideration hemodynamic, morphological, and clinical parameters, accurately predicts aneurysm re-treatment. Calculation of RP before embolization may be able to predict the aneurysms that will require re-treatment.